The Implementation Of The Steam Approach With Indonesia’s Local Culture In Mathematics Learning: A Systematic Literature Review - Nafiqoh Elsa Kartikaningtyas; Sri Subanti; Budi Usodo; Farida Nurhasanah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The demands of 21st-century education require learning approaches that foster critical thinking, creativity, collaboration, and communication. Integrating Science, Technology, Engineering, Arts, and Mathematics (STEAM) is seen as a promising strategy to address these needs, yet its systematic implementation in mathematics learning in Indonesia, especially with local cultural contexts, remains underexplored. This study aimed to investigate how the STEAM approach has been applied in Indonesian mathematics education and how local culture is integrated. A systematic literature review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to ensure transparency and rigor during the identification, screening, eligibility, and inclusion phases. The initial search yielded 259 articles from Scopus, ERIC, SINTA, Web of Science, and OpenAlex databases. After applying inclusion and exclusion criteria and removing duplicates, 20 articles published between 2014–2024 were analyzed in depth. To identify research trends, a bibliometric analysis using VOSviewer was performed to map keyword co-occurrences. The findings reveal that while the STEAM approach, combined with elements such as local art, traditional games, and architecture, successfully enhances student engagement and contextual learning, its application largely emphasizes procedural rather than conceptual understanding. Moreover, interdisciplinary collaboration and integration of local culture are not yet fully optimized to develop higher-order thinking. This review highlights the need for future studies to strengthen conceptual depth, promote authentic cross-disciplinary learning, and incorporate broader cultural perspectives in designing culturally responsive STEAM-based mathematics education.